Music as Social Reflection: A Sociology of Literature Study of Bob Marleyâ€™s â€œOne Love/People Get Ready - Sulltan Baldy Yusuf,; Said Kholil Amrullah,; Elleora P. Sitinjak,; M. Dhevano Qafkha Qubrey,; T. Thyrhaya Zein, (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2026)
This journal discusses Bob Marleyâ€™s song â€œOne Love/People Get Readyâ€ as a work ofmusical literature that conveys messages of unity, peace, and human solidarity. This song servesnot only as entertainment but also as a medium for social reflection that depicts a society markedby conflict, discrimination, and injustice. The objective of this study is to analyze the meaning ofthe songâ€™s lyrics and identify their relevance to social reality, particularly in efforts to fosterharmony amidst diversity. Additionally, this study aims to examine how the moral messages in thesong can contribute to the formation of collective social consciousness.The method used in this study is a qualitative method with a literary sociology approach.Data were collected through literature review and textual analysis of song lyrics, then analyzedusing descriptive-analytical techniques to uncover the symbolic meanings and social messagescontained within them. This approach allows the researcher to understand the relationship betweenmusical works and the social context underpinning them.The results of the study indicate that this song contains a universal message about theimportance of love, unity, and tolerance as solutions to various social problems. In conclusion, thissong serves not only as a work of entertainment but also as an educational tool capable of fosteringpeace and social justice within the global community.Keywords: Bob Marley, One Love, Sociology of Literature, Social Solidarity, Peace Education.